(untitled) (World Bulletin of Management and Law, 2023)
This article presents some aspects of the activities of the prosecutor’s office in the field of combating torture. The opinions expressed by scientists in this field are analyzed. The author expressed his opinion about the ongoing reforms in the field of combating torture in our country